Identification of differentially expressed genes in mouse paraspinal muscle in response to microgravity - Li, Yongjin; Kong, Chao; Wang, Baobao; Sun, Wenzhi; Chen, Xiaolong; Zhu, Weiguo; Ding, Junzhe; Lu, Shibao (Frontiers in Endocrinology, 2022)
Low back pain (LBP) is the primary reason leading to dyskinesia in patients, which can be experienced by people of all ages. Increasing evidence have revealed that paraspinal muscles (PSM) degeneration (PSMD) is a causative contributor to LBP. Current researches revealed that fatty infiltration, tissue fibrosis and muscle atrophy are the characteristic pathological alterations of PSMD, and muscle atrophy is associated with abnormally elevated oxidative stress, reactive oxygen species (ROS) and inflammation. Interestingly, microgravity can induce PSMD and LBP. However, studies on the molecular mechanism of microgravity in the induction of PSMD is strongly limited. This study identified 23 DEGs in PSM (longissimus dorsi) of mice which flown aboard the Bion M1 biosatellite in microgravity by bioinformatics analysis. Then we performed PPI, Go function, and KEGG pathway enrichment analysis for the DEGs. We found that Il6ra, Tnfaip2, Myo5a, Sesn1, Lcn2, Lrg1, and Pik3r1 were inflammatory genes; Fbox32, Cdkn1a, Sesn1, and Mafb were associated with muscle atrophy; Cdkn1a, Sesn1, Lcn2, and Net1 were associated with ROS; and Sesn1 and Net1 linked to oxidative stress. Furthermore, Lcn2, Fbxo32, Cdkn1a, Pik3r1, Sesn1, Net1, Il6ra, Myo5a, Lrg1, and Pfkfb3 were remarkably upregulated, whereas Tnfaip2 and Mafb were remarkably downregulated in PSMD, suggesting that they might play a significant role in regulating the occurrence and development of PSMD. These findings provide theoretical basis and therapeutic targets for the treatment of PSMD.